Online Identity Analysis of Public Figure Deddy Corbuzier on Instagram Account @Mastercorbuzier: Analisis Identitas Online Tokoh Publik Deddy Corbuzier pada Akun Instagram @Mastercorbuzier - Listianto, Abdul Yudha Fahrezha; Fibisono, Pandu Bagus; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
In the digital age, social media, especially Instagram, has played an important role in shaping one's identity and public image. Deddy Corbuzier, an Indonesian influencer and celebrity, uses this platform to project his self-image through consistent and authentic content. This research investigates how he manages his digital identity in the face of challenges such as context collapse meeting audiences with diverse backgrounds as well as risks such as cyberbullying and privacy violations. The findings show that Deddy implements adaptive communication strategies and maintains authenticity despite being faced with criticism. In addition, the study discusses potential proactive measures to deal with such risks, including strengthening data protection regulations and increasing public awareness. By strategically utilizing social media, individuals can not only build strong personal branding but also create a safer digital ecosystem. Highlights: Adaptive Digital Identity Management – Deddy Corbuzier navigates context collapse by tailoring his communication while maintaining authenticity to engage diverse audiences. Handling Risks and Criticism – He employs strategies to manage cyberbullying and privacy concerns, balancing transparency with personal boundaries. Proactive Digital Safety Measures – Strengthening data protection laws and public awareness can enhance both personal branding and a safer online environment. Keywords: Online Identity, Instagram, Public Figure, Deddy Corbuzier